Transparent chiral polymers for optical applications - Pujari, N. S.; Kulkarni, M. R.; Large, M. C. J.; Bassett, I. M.; Ponrathnam, S. (Journal of Applied Polymer Science, 2005)
Optically active chiral polymers and copolymers of cholesteryl methacrylate have been studied for use in optical applications including plastic optical fibers. Homopolymers of chiral cholesteryl methacrylate with differing molecular weights and copolymers with methyl methacrylate were synthesized by free-radical copolymerization in tetrahydrofuran using azobisisobutyronitrile at 67 degrees C for 26 h. All polymers were characterized for molecular weight, glass-transition temperature, optical rotation, transparency, and refractive index and solution blended to test for compatibility with poly(methyl methacrylate). Such chiral materials are of particular interest because they offer useful polarization properties without requiring bulk orientation of the molecules. This makes it possible to produce low cost optical elements such as circularly birefringent or circularly polarizing optical elements with potential applications in polarization manipulations and sensing. (c) 2005 Wiley Periodicals, Inc.
Keywords: chiral; cholesteryl methacrylate; optically active; plastic optical fiber; poly(cholesteryl methacrylate); poly(cholesteryl methacrylate-co-methyl methacrylate)

Thermotropic behavior of lithocholic acid derivative linked hydroxyethyl cellulose - Shaikh, V. A. E.; Maldar, Noormahamad N.; Lonikar, Shrikant Vitthal; Rajan, C. R.; Ponrathnam, S. (Journal of Applied Polymer Science, 2006)
Various mesogenic lithocholic acid (LA) derivatives [3-acetyl LA (LAAC); 3-propionyl LA (LAP), 3-cinnamoyl LA (LACin); 3-benzoyl LA (LAB), 3-(4-nitrobenzoyl) LA (LANB); and methyl-3-(3-carboxypropionyl) LA, i.e., LA methyl ester monosuccinate (LAMeMS)] were reacted with hydroxyethyl cellulose (HEC) to obtain a series of LA derivatives of HEC. These polymers were characterized by the mesogen content, 1.1, differential scanning calorimetry, and hot-stage coupled polarizing optical microscopy. The degree Of Substitution (DS) ranged from 0.27 to 1.11. Polymers HEC-LAB (DS = 1.11), HEC-LANB (DS = 0.80), HEC-LACin (DS = 0.76), and HEC-LAP (DS = 0.27) exhibited a mesophase on heating whereas HEC-LAB also showed a mesophase on cooling. The other polymers HEC-LAAC (DS = 0.89) and HEC-LAMeMS (DS = 0.36) did not reveal mesophase formation with either heating or cooling. It is observed that the formation of a mesophase is affected by the type of mesogen that is used rather than the mesogen content of the polymer. (c) 2006 Wiley Periodicals, Inc.
Keywords: hydroxyethyl cellulose; lithocholic acid; thermotropic